Growing a race : Nellie L. McClung and the fiction of eugenic feminism - Devereux, Cecily Margaret, 1963- (McGill-Queen's University Press, 2005)
"In recent scholarship, the extent to which Nellie McClung was implicated in the passage of eugenical legislation in Canada has created ambivalence around her legacy as one of the most popular figures in early twentieth-century women's rights activism. Cecily Devereux situates McClung's fiction within the context of her social reform work and the ways in which that work can be understood to be broadly eugenic or concerned with the preservation of race."--Jacket